Photon counting statistics using a digital oscilloscope - Martinez Ricci, Maria Luz (2007)
We present a photon counting experiment designed for an undergraduate physics laboratory. The statistics of the number of photons of a pseudo-thermal light source is studied in two limiting cases: much longer and much shorter than the coherence time, giving Poisson and Bose-Einstein distributions, respectively. The experiment can be done in a reasonable time using a digital oscilloscope without the need of counting boards. The use of the oscilloscope has the advantage of allowing the storage of the data for further processing. The stochastic nature of the detection phenomena adds additional value because students are forced to do data processing and analysis.